Penambahan Polen Aren Sebagai Pakan Lebah untuk Meningkatkan Bobot Koloni Lebah Madu Trigona sp. - IKetut Gede Wiryawan; Erwan Erwan; Lilis Juniarti (Jurnal Ilmu dan Industri Peternakan, 2022)
The aim of this study was to determine the effect of feed supplement in the form of sugar palm pollen on the increase in colony weight of Trigona sp. The study was conducted in Lembah Sari Village, Batulayar District, West Lombok Regency, which lasted for 4 weeks from May 2020-June 2020. Ten honey bee colonies of Trigona sp. were randomly assigned to two treatment groups with five replications each according to a completely randomized design. The treatment without palm pollen was placed differently with a distance of ±600 meters from the treatment using palm pollen and the distance between replicates was ±1 meter. The stages of the research include making the hive, selecting a colony from glodok, moving the colony to the hive, placing the research hive, and placing the palm pollen. The variables observed included the number of pollen cells and colony weights. The results showed that mean values for the number of pollen cells treated without and with palm pollen treatment from weeks 1-4 were 6,2±0,45, 7,0±0,71, 9,0±0,71, 12,2±0,84 and 6,4±0,55, 8,4±1,14, 11,8±0,84, and 15,4±1,14 respectively. While the colony weight for those with or without supplement were 0,15±0,04, 0,29±0,05, 0,44±0,05, 0,64±0,06 and 0,14±0,01, 0,39±0,09, 0,53±0,03, and 0,80±0,08. The average number of pollen formed and the colony weight for those given supplement was significantly higher than those without feed supplement. Thise results indicate the important of providing feed supplement in order to sustain productivity of Trigona sp.